2015
DOI: 10.1016/j.ebiom.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anti-tumor Cells Carrying Natural Killer (NK) Cell Antigens in Patients With Hematological Cancers

Abstract: Natural killer (NK) cells, a cytotoxic lymphocyte lineage, are able to kill tumor cells in vitro and in mouse models. However, whether these cells display an anti-tumor activity in cancer patients has not been demonstrated. Here we have addressed this issue in patients with several hematological cancers. We found a population of highly activated CD56dimCD16+ NK cells that have recently degranulated, evidence of killing activity, and it is absent in healthy donors. A high percentage of these cells expressed nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
67
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(79 citation statements)
references
References 67 publications
11
67
1
Order By: Relevance
“…It is possible that activation-induced isoform switching occurs in vivo at sites of viral infection or malignancy, but only those cells that revert back to a CD45RA + CD45ROphenotype can efficiently re-enter the peripheral blood. Although CD45RO expression is virtually absent on peripheral blood NK cells isolated from healthy individuals, distinct subsets of CD45RO + cells have been identified in the blood and bone marrow of individuals with various types of hematologic malignancies (60).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that activation-induced isoform switching occurs in vivo at sites of viral infection or malignancy, but only those cells that revert back to a CD45RA + CD45ROphenotype can efficiently re-enter the peripheral blood. Although CD45RO expression is virtually absent on peripheral blood NK cells isolated from healthy individuals, distinct subsets of CD45RO + cells have been identified in the blood and bone marrow of individuals with various types of hematologic malignancies (60).…”
Section: Resultsmentioning
confidence: 99%
“…While we observed trends for increased expression of CD27 in NK cells that persisted across WB and BM samples, and while there are conflicting hypotheses around the functional role of NK cells with this phenotype (32)(33)(34)(35), the observed trends toward increased signal intensity of CD137 combined with increased levels of activation markers CD69 and CD25 may suggest any compromised cytolytic activity could be offset to allow for daratumumab-mediated antibody-dependent cellular cytotoxicity (32). Furthermore, Krzywinska et al showed that in hematologic malignancies, NK cells with an immature profile are still able to show cytotoxic activity (36,37), and Wang et al showed that post-daratumumab NK cells are more effective at eradicating myeloma cells (38). Recently, Feng et al have demonstrated that isatuximab, another CD38-targeted monoclonal antibody, promotes NK-cell activity through interferon γ induction, as evidenced by CD107a upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…They constitute a heterogeneous cell population with distinct phenotypic and functional characteristics, including, but not limited to, their ability to mediate cytolytic activity (27, 28). NK cell activity is regulated by the equilibrium between signals transduced by inhibitory and activating receptors, which dictates target cell elimination and pro-inflammatory cytokine production (29, 30).…”
Section: Introductionmentioning
confidence: 99%